Bosnia and Herzegovina : Sixth and Seventh Reviews Under the Stand-By Arrangement and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report, 2001)
The Stand-By Arrangement with Bosnia and Herzegovina was approved on May 29, 1998. Bank regulation and supervision have been strengthened over the past year, although procedures continue to fall short of best practice in some areas. The authorities have reformed the sales tax regime to equalize tax rates in the two entities, broaden and unify the base, and simplify the tax system in a broadly revenue neutral manner. IMF staff urged the authorities to accelerate the implementation of modern treasuries.